KEANEKARAGAMAN JENIS TUMBUHAN TINGKAT POHON PADA HUTAN RAWA GAMBUT DI TAMAN WISATA ALAM BANING KABUPATEN SINTANG - Sudaryanti, Yunus; Muin, Abdurrani; Manurung, Togar Fernando (JURNAL HUTAN LESTARI, 2014)
Diversity of tree species in peat swamp forest in the natural park Baning Kabupaten Sintang, until now unknow condition of tree species diversity and tree species, discruption of habitat as a result of plant. Therefore it is necessary to study diversity of tree species in peat swamp forest in the Natural Park Baning. General purpose research keanekaragaman want to know the level of woody plant species in peat swamp forest in the Natural Park Baning, species purpose like to obtain information about the type of dominant vegetation types. The length of time for two month to study the preparation of the thesis. Research using a survey method with the path system, where the manufacture of the plot carried out continuously on the path to the observation. Methods of data collection in this study consisted of primary and secondary data collection. Based on data obtained shows the composition and structure of tree plants whose value varies with the type contained in the peat swamp forest in The Natural Park Baning, the result of extensive research shows 3,64 ha with 3 lines of observations there were 39 species with a total of 985 individuals. 3 lines of the track I, II, III type which has the highest importance value index is engretak kind (Dipterocarpus grandiflorum) of 56,6166 % and the lowest importance value index obtained entepung kinds (Dillenia sp) of 0,2618%. of old data by Kayoman (2002) mentioned there are 57 types of trees, but that is only found in the current study 39 species only, meaning that there has been a decline.Consequently a decline in ecosystem function that threatens watersheds highly significant influence on the stands. Keyword : Diversity, species in peat swamp forest, consequently a decline in ecosystem function